1994
DOI: 10.1016/0014-5793(94)80367-6
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of PC12 cells in response to a cAMP analogue is accompanied by sustained activation of mitogen‐activated protein kinase

Abstract: It has been proposed previously that the sustained activation of mitogen-activated protein kinase may be necessary for the differentiation of PC12 cells. Differentiation of PC12 cells is induced by many extracellular agonists including nerve growth factor (NGF) and cyclicAMP analogues, but not epidennal growth factor (EGF), insulin or phorbol esters. Our results demonstrate that: (i) 8-(4-chlorophenylthio)-cyclicAMP (CPT-CAMP) activates MAP kinase; this raises the possibility that the MAP kinase pathway may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 29 publications
5
90
0
Order By: Relevance
“…The activation of MAP kinase by cAMP has been suggested to be involved in the neuronal differentiation of PC12 cells (3,16,51,52) and the melanogenesis in melanoma cells (46). In light of these observations it is interesting that PYS-2 cells resemble parietal endoderm cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of MAP kinase by cAMP has been suggested to be involved in the neuronal differentiation of PC12 cells (3,16,51,52) and the melanogenesis in melanoma cells (46). In light of these observations it is interesting that PYS-2 cells resemble parietal endoderm cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of signalling by the MAP kinase cascade in terms of either cellular proliferation or cellular differentiation is currently under intensive study and recent reports using other cell types have suggested a role for chronic MAP kinase activation in causing exit from the cell cycle followed by cellular differentiation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…1). Although the PAC1 receptor couples to both G q and G s G proteins, PACAP-mediated neuritogenesis in PC12 cells is believed to proceed through cAMP because cAMP analogs or cAMP elevation with forskolin mimic the effects of PACAP (16,(20)(21)(22). In addition, neuritogenesis induced by PACAP is blocked by the cAMP antagonist dideoxyadenosine (22), and there is currently no evidence that direct activation of G q -mediated signaling mediates differentiation in PC12 cells.…”
mentioning
confidence: 99%
“…The critical link missing from these studies is the component responsible for cAMPdependent PKA-independent activation of ERK in PC12 cells (3,13,16,20 (24) (Fig. 2).…”
mentioning
confidence: 99%